(untitled) (The Pretoria Student Law Review, 2021)
This note discusses the critical facts controlling the issues of the FEDSAS case, the court’s holding and reasoning thereof, prior litigation regarding admissions to public schools and how the court’s decision actualises the right envisaged in section 29(1)(a).